Biophysical and Structural Studies on the Capsid Protein of the Human Immunodeficiency Virus Type 1: A New Drug Target? - José L. Neira (The Scientific World Journal)
AIDS affects 30 million people worldwide and is one of the deadliest epidemics in human history. It is caused by a retrovirus, HIV, whose mature capsid (enclosing the RNA with other proteins) is formed by the assembly of several hundred copies of a protein, CA*. The C-terminal domain of such protein, CAC, is a driving force in virus assembly and the connections in the mature capsid lattice indicate that CAC joins through homodimerization of the CA hexamers. In the first part of this work, I shall review the biophysical studies carried out with the dimeric wild-type CAC protein and a mutant monomeric variant. The results open new venues for the development of drugs able to interact either with the dimeric species, hampering its assembly, or with the monomeric species, obstructing its folding. In the second part of this review, I shall describe the structures of complexes of CAC with small molecules able to weaken its dimerization. Furthermore, interactions with other proteins and lipids are also described. The whole set of results suggests that much of the surface of CAC does not accommodate binding per se, but rather binding sites in the protein are predefined, i.e., there are “hot” spots for binding in CAC (whatever be the molecule to bind). These “hot” residues involve most of the dimerization interface (an α-helix) of the CAC wild-type protein, but also polypeptide patches at the other helices.